INVENTARISASI PERMAINAN TRADISIONAL JAWA SEBAGAI SARANA PENDIDIKAN KARAKTER DALAM PEMBELAJARAN BAHASA INDONESIA PADA SISWA SEKOLAH DASAR - Eni Winarsih (Widyabastra : Jurnal Ilmiah Pembelajaran Bahasa dan Sastra Indonesia, 2014)
The purpose of this research are (a) describe the development process of traditional Java games to impart  character education in Indonesian learning ; (b) to test the feasibility and effectiveness of the use of traditional Java games to impart character education in learning Indonesian. Development method used in this research is the development model Borg and Gall which includes 4 stages, namely: (1) preliminary or exploratory studies, (2) the stage of prototype development,  (3) the stage of prototype testing or experimentation, and  (4) the introduction or implementation of products or dissemination. The final result of this development research is a form of traditional game guide books used in learning Indonesian namely Engkling game Instructions Book, Egrang Treasure Game Instruction Book, and Language Dakon Games Instruction Book. The effectiveness of using traditional Java games is to impart character education in Indonesian language learning for elementary school proved effective with demonstrated achievement of specified indicators, namely the students happy and enthusiastic, train students' language skills, mental training, cooperation, honesty students. Results of tests for Indonesian lesson shows that the average score of the class reached 81.65 and 82.45, it is already up to the KKM and it is specified, then the results of the field study Indonesian study using traditional games are considered successful.